Conocimiento sobre VIH/SIDA y comportamientos sexuales de riesgo en adolescentes de bachillerato de la Unidad Educativa 12 de Febrero - Sánchez Ochoa, Juleidy Cristina (2022)
The limited knowledge about HIV/AIDS has contributed to the increase of this infection, adolescents being the most affected population. This, along with unprotected sexual practices, have caused an increase in the risk of transmission of sexually transmitted infections (STIs), including HIV/AIDS, which cause various health problems, marking the life of the adolescent. In this context, the present research work was carried out with the objective of determining the level of knowledge adolescents at the Unidad Educativa 12 de Febrero high school in the city of Zamora have about HIV/AIDS and its relation to risky sexual behaviors. In this cross-sectional study, whose universe consisted of 1710 students and a total sample of 300 students of second and third years of high school, who were given a validated survey, the following results were obtained: the majority of female and male adolescents aged between 15-17 years (88,06%) and over 17 years (94,29%) respectively have adequate knowledge about HIV/AIDS, likewise, a large percentage of students who have started their sexual life have adequate sexual behaviors, mainly women over 17 years of age (72,73%) and men aged 15-17 years (68,57%). In addition, the relationship between both variables was established by calculating the Spearman correlation coefficient obtaining a value p = 0.4, accepting the null hypothesis, which indicates that adolescents' knowledge is not related to risky sexual behaviors. It was concluded that the level of knowledge about HIV/AIDS does not influence the sexual behavior that adolescents practice